Seepage-induced consolidation test mine tailings - Tian, Zhengguang, author; Bareither, Christopher A., advisor; Scalia, Joseph, advisor; Bailey, Travis S., committee member (Colorado State University. Libraries, 2017)
The objectives of this research were to design, construct, and evaluated the seepage induced consolidation testing (SICT) apparatus. Design of the SICT apparatus was based on existing apparatus at the University of Colorado-Boulder and University of British Columbia. Three materials were evaluated by the SICT and the odometer test to validate apparatus functionality: kaolin clay, fine synthetic tailings (FST), and average synthetic tailings (AST). This study consisted of the following tasks: (i) design and construction of the SICT apparatus; (ii) evaluation of geotechnical characteristics of kaolin clay, FST, and AST; (iii) conducting SICTs on kaolin clay, FST, and AST to determine the compressibility and hydraulic conductivity constitutive relationships; (iv) evaluation and comparison of the constitutive relationships of these materials with two constitutive models based on data from SICT; (v) conducting odometer tests on the same three materials to compare with results from the SICT; and (vi) evaluation of the effects of slurry composition on consolidation behavior (i.e., void ratio versus effective stress, e-σ', and hydraulic conductivity versus void ratio, k-e). The results of tasks i-vi support that the SICT apparatus constructed at Colorado State University (CSU) was reliable and repeatable based on benchmark tests conducted on kaolin clay. Constitutive relationship models generated from possible permutations of the seepage test and step loading test that comprise the SICT show a strong correlation. These models are compared to a composite model that combines all seepage and loading phases for a given SICT. The two models yield similar constitutive model parameters. Consolidation behavior (e-σ' and e-k) of kaolin clay, FST and AST show a wide range of behavior due to the different material grain size distributions.